2020
DOI: 10.1002/iid3.392
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐425‐3p inhibits myocardial inflammation and cardiomyocyte apoptosis in mice with viral myocarditis through targeting TGF‐β1

Abstract: Objective Emerging articles have profiled the relations between microRNAs and viral myocarditis. This research was unearthed to explore the capacity of miR‐425‐3p on cardiomyocyte apoptosis in mice with viral myocarditis and its mechanism. Methods A total of 120 mice were classified into 4 groups in a random fashion (n = 30). The mice were intraperitoneally injected with coxsackievirus type B3 (CVB3) to induce myocarditis. On the 7th day after CVB3 infection, 10 mice in each group were euthanized to assess the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Studies have shown that upregulation of miR-425-3p reduced cardiomyocyte apoptosis and alleviate myocardial inflammation in mice with viral myocarditis, thus improving their survival rates. [ 38 ] In addition, the relationship between autophagy and apoptosis is complex. Upon starvation or other stress conditions, autophagy is induced, and when stress persists, apoptotic are activated.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that upregulation of miR-425-3p reduced cardiomyocyte apoptosis and alleviate myocardial inflammation in mice with viral myocarditis, thus improving their survival rates. [ 38 ] In addition, the relationship between autophagy and apoptosis is complex. Upon starvation or other stress conditions, autophagy is induced, and when stress persists, apoptotic are activated.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, data suggest that plasma upregulation of miRNA 155 is associated with coronary slow flow [ 35 ]. Literature on miRNAs 30b-5p, 30c-5p, 103a-5p, 140-3p, 185-5p 221-3p and 425-3p shows regulatory properties in atherosclerosis as well as cardiomyocyte apoptosis and necrosis [ 21 , 36 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-497-5p (Zhao et al, 2020), microRNA-150-3p (Qiu et al, 2020), miR-708-5p (Wang et al, 2020), and microRNA-497-5p (Liu et al, 2020a) have been shown to promote this process, while miR-30 (Zhang et al, 2020a), miR-129-5p (Yin et al, 2020), miR-128-3p (Zhang et al, 2020b), and miR-17-5p have suppressive effects. In various cell types, miR-425-3p is differentially expressed (Li et al, 2020;Ma et al, 2019), but its function in osteogenesis has not been documented. The MC3T3-E1 pre-osteoblast cell line has been widely used for in vitro osteogenesis research (Lv et al, 2017).…”
Section: Discussionmentioning
confidence: 99%